Treatment of cervical ectopic pregnancy by modified Shirodkar type cerclage. A case series. - Carpio-Guzmán, Luis Alberto (2023)
Introduction. Cervical ectopic pregnancy is a challenge both in diagnosis and in its treatment. Hysterectomy is no longer the most widely used treatment, with medical and minimally invasive treatments being the most widely used. Objective. To describe the efficacy of the Shirodkar-type cervical cerclage in the management of cervical pregnancy. The study. It is presented a case series treated at the Instituto Nacional Materno Perinatal in pregnant women attended between 2015 and 2021. The modified Shirodkar cervical cerclage technique was performed for hemostatic purposes, so that it allows us to aspirate the gestational sac contained in the cervical canal, preventing bleeding. Finding. Six cases of cervical ectopic pregnancy were treated with the modified Shirodkar technique, all of them successfully, since the embryonic tissue contained in the cervical canal was evacuated, controlling post-evacuation bleeding, not requiring additional treatments or hysterectomy. Conclusion. The evaluation of this series of cases allows us to conclude that the modified Shirodkar-type cervical cerclage technique, in the treatment of cervical ectopic pregnancy, it is effective in controlling the potential bleeding that can occur after the evacuation of embryonic tissue located in the cervical canal, as well as avoid additional treatments or hysterectomy.